Identity Construction in Mathematics Learning: A Phenomenological Study of Girl Students - Adhikari, Krishna Prasad (Interdisciplinary Research in Education, 2019)
This phenomenological study examined how girl students struggle in constructing their identity in mathematics learning. The concept given by Cobb and Hodge (2003) was used as a theoretical basis to explain the identity construction of girls. In addition, the process of identity construction is critically examined through a feminist perspective. Three girl students studying mathematics in Master’s level were involved in in-depth interview. The data collected through interview were first transcribed, which was followed by thematic network analysis to make meaning from the information. The key finding was that students faced difficulties and struggle due to patriarchal system of society, false beliefs about mathematics and mathematics learning, and traditional and meritocratic system of teaching learning system.